2013
DOI: 10.5005/jp-journals-10006-1224
|View full text |Cite
|
Sign up to set email alerts
|

Three ‘Delays’ as a Framework for Critical Analysis of Maternal Near Miss and Maternal Mortality

Abstract: Objective: The aim of the study was to assess the magnitude and causes of three delays and their possible implications for safe motherhood. Methods:The cross-sectional prospective study was carried out over a period of 1 year from January to December 2010. All patients who fulfill the WHO criteria for maternal near miss and all cases of maternal death during this period were included in the study. The various factors responsible for the delays in accessing obstetrics care facilities at all the three levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…In our study, delays related to supplier or provider side were less observed in 19 percent of maternal deaths. The third delay is relatively rarely reported as compared to first and second delays in the previous literature [28, 29]. Type 3 delay is directly indicative of suboptimal quality of care and it is also reflected in our study [6].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In our study, delays related to supplier or provider side were less observed in 19 percent of maternal deaths. The third delay is relatively rarely reported as compared to first and second delays in the previous literature [28, 29]. Type 3 delay is directly indicative of suboptimal quality of care and it is also reflected in our study [6].…”
Section: Discussionsupporting
confidence: 56%
“…It is observed in many studies that public transportation may not be accessible at the time required or may take a considerable time to arrive at the health facility [27]. In our low socio-economic settings, earning daily wage may be prioritized over transportation expenses for reaching health facility at the time of complications [8, 28]. Pregnant women require health care services closer to them or promptly accessible affordable public transport as a solution for the type 2 delay.…”
Section: Discussionmentioning
confidence: 99%
“…In our study first delay was present in 71% cases in MNM group and 90% in maternal death group. It corresponds with the study conducted by Yunus et al 12 in which the first delay was observed as the major cause of delay in 80% of the patients in both the groups.…”
Section: Discussionsupporting
confidence: 91%
“…19 The socioeconomic status (SES) was defined by Kuppuswamy's socioeconomic status scale modified to the Nepalese context. 20 This scale categorizes the family into upper (26)(27)(28)(29), middle (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and lower (< 10) socio-economic status. 20 Enabling factors include exposure and knowledge related to reproductive health such as use of family planning methods (yes/no), place of availability of family planning devices (yes/no) and discussion with others/health workers (yes/no), immunization (yes/no), breast feeding (yes/no), HIV/AIDS (yes/no).…”
Section: Methodsmentioning
confidence: 99%
“…7,8 Men's active involvement plays a vital role in a reduction of three delays: delay in decision to seek care; delay in reaching care; and delay in receiving care. [9][10][11] Therefore, when men are the sole decision makers, men need to be well aware of the needs during pregnancy, delivery and childbirth. Several studies have reported advantages of male involvement in MHCPs: increased contraceptive usage, improved maternal mental health, increased access to antenatal and postnatal care services, and reduced unhealthy practices such as smoking during pregnancy.…”
Section: Introductionmentioning
confidence: 99%